Forests, trees and human health - Nilsson, Kjell; Nilsson, Kjell (Springer, 2011)
The link between modern lifestyles and increasing levels of chronic heart disease, obesity, stress and poor mental health is a concern across the world. The cost of dealing with these conditions places a large burden on national public health budgets so that policymakers are increasingly looking at prevention as a cost-effective alternative to medical treatment. Attention is turning towards interactions between the environment and lifestyles. Exploring the relationships between health, natural environments in general, and forests in particular, this groundbreaking book is the outcome of the Eu.